Weeding out the Roots? Migrant Identity in A.M. Bakalar’s Polish-British Fiction - Bryla, Martyna (Complutense Journal of English Studies, 2020)
Poles are one of the largest non-UK born ethnic groups in all countries and most regions of the United Kingdom. Since Poland’s accession to the European Union in May 2004, thousands of Poles have migrated to the UK, hoping for better professional opportunities and higher standards of living. It was thus only a matter of time before Poles started to put their experience of migration on paper. One example is A.M. Bakalar, whose literary debut, Madame Mephisto (2012), was promoted as the voice of the new wave of Polish migration and the first novel to be written in English by a Polish female author since Poland joined the EU in 2004. This article centres on Bakalar’s protagonist, a thirty-year-old Pole in London, with the aim of revealing how cultural myths and beliefs feed into the process of identity formation and what it takes for the experience of migration to go awry. By exploring Magda’s problematic relationship with her home country, represented as oppressive and insular, this article inquiries into the nature of contemporary migrant experience and the role which national identity plays in the process of cultural adjustment.